Phenotypic and growth characterization of human mesenchymal stem cells cultured from permanent and deciduous teeth - Revathi Shekar; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2012)
Context: A step-by-step approach to harvesting stem cells from the pulp of permanent and deciduous teeth, the problems faced during culture, and the differences in the growth properties and morphology of cells obtained from both the sources has been discussed as a precursor to the use of these cells in therapy. Aims: To isolate, culture, and study the morphology and growth characteristics of mesenchymal stem cells from the dental pulp of permanent teeth (dental pulp stem cells; DPSC) and exfoliated deciduous teeth (stem cells from human exfoliated deciduous; SHED). Settings and Design : Cell culture study carried out at the Department of Oral and Maxillofacial Pathology, Ragas Dental College and Hospital, Chennai. Materials and Methods: Fifteen permanent teeth and thirteen deciduous teeth from ten subjects were used. The growth characteristics and phenotype of cultured DPSCs and SHED were studied from the fourth passage on 24-well plates. Statistical analysis used : Data analysis was done using SPSS ® version 10.05. Linear regression analysis was performed to derive the slope from growth curves and Mann-Whitney U test was performed to compare the fibroblastoid: epithelioid cell ratio between permanent and deciduous tooth pulp groups. Results: Protocol for the culture of DPSC and SHED was standardized. DPSC and SHED populations were morphologically distinct. The cells from permanent tooth pulp showed a higher proportion of spindle-shaped fibroblastoid cells, whereas deciduous pulp culture showed a higher proportion of epithelioid cells. The seeding efficiency of DPSC - 88.9% (14 th permanent tooth pulp) and 91.7% (15 th permanent tooth pulp) was higher as compared to SHED - 84.25% (10 th deciduous tooth pulp). Conclusions: Permanent and deciduous teeth are both viable sources of stem cells. The permanent teeth were easier to culture because of a lower chance of contamination with oral microflora. The growth characteristics of the cells obtained from both these sources were similar. However, there was a difference in the ratio of fibroblastoid cells to epithelioid cells between the cultures obtained from the permanent and deciduous teeth.